Effects Of The Use Of Calculators, The Polya Heuristic and Worked Examples On Performance in Learning Mathematics From a Cognitive Load Perspective - Aeria, Lawrence Aloysius (2004)
Cognitive load theory holds that if an instructional format reduces extraneous cognitive load andlor increases germane cognitive load during learning, as compared to another instructional format, then it will be more efficient in promoting learning, provided that the total cognitive load does not exceed the total mental resources. Based on this premise, a series of four experiments was conducted to investigate the use of calculators, the Polya heuristic and worked examples in an attempt to generate an alternative instructional format that is more instructionally efficient than the conventional one to teach Percentage to Form 1 students. It was hypothesized that the use of calculators and the use of worked examples can reduce cognitive load during leaming and lead to better learning performance while the use of the Polya heuristic increases cognitive load and reduces learning performance. The results from the experiments indicated that the use of calculators and worked examples reduced cognitive load and led to better learning performance but the use of the Polya heuristic produced zero effects. Based on the results from the experiments, an alternative instructional format, called the calcworked instructional format, that incorporated the use of calculators and the use of partial completion worked examples was generated. The calcworked instructional format was compared with the conventional instructional format and was found to be more instructionally efficient.